Inhibition of autophagy enhances synergistic effects of Salidroside and anti-tumor agents against colorectal cancer - Hai Li; Chen Chen (BMC, 2017)
Abstract Background Various plant extracts have been suggested to be used as auxiliary agents in chemotherapy considering their anti-proliferative effect on cancer cells. However, recent reports reveal that plant extracts may function as inducers of autophagy of cancer cells. In general, autophagy confers survival advantage for cells responding to stress conditions, thus representing an important mechanism for chemo-resistance. This study was aimed to investigate the effectiveness of combined use of Salidroside (Sal, a phenylpropanoid glycosides from Rhodiola rosea L) with anti-tumor agents against colorectal cancer (CRC) cells, and moreover to evaluate the potential role of autophagy in the combined therapy. Methods CRC cells, HCT-116, were incubated with Sal alone or in combination with conventional chemotherapy agents including oxaliplatin (OXA), 5-fluorouracil (5-FU) and Doxorubicin (ADM). Cell proliferative characteristics were evaluated by cell viability and apoptosis rate. The protein expression was assessed by Immunofluorescent and Western blot assays. Results Sal, alone or in combination with anti-tumor agents, increased expression of autophagic biomarkers, including LC3B and Becline-1, suggesting an autophagy induction. Except for the up-regulation of p-AMPK, p-mTOR, p-NF-κB (p65), TGF-β, p-JAK2 and p-STAT3 were down-regulated by Sal. Because autophagy is positively correlated with the activation of AMPK/mTOR, NF-κB, TGFβ1 and JAK2/STAT3 cascades, the autophagy induced by Sal may associate with AMPK activation. Indeed, blockage of AMPK signaling via Compound C or AMPK knockdown inhibited the autophagy. The blockage of AMPK signaling or a direct inhibition of autophagy via 3-MA increased effectiveness of combined use of Sal with anti-tumor agents against CRC. Conclusions Inhibition of autophagy enhances synergistic effects of Sal and anti-tumor agents against colorectal cancer. This study provides experimental evidence and theoretical reference for improvement of a novel chemotherapy treatment protocol.